A Common Worm in a Rare Place. - Mohammed Reza Sheikhian (Tehran University of Medical Sciences, 2013)
A case of a 40-year-old female, in whom a 6-meter long worm (Taenia saginata) was found in stomach, is reported here. In this patient, T. saginata upward migration of the worm to the stomach, its rare phenomenon, worm mostly seen in the small intestine. This is mainly because of the high gastric acidity. In this patient, we believe proton pump inhibitor (PPI) use caused hypochlorhydria and coexistence H. pylori infection caused chronic atrophic gastritis, which resulted in the retrograde migration of the tapeworm to the stomach in our patient.